Ruiz-Corbella, M. & García-Gutiérrez, J. (Eds.) (2023). Service learning: Scenarios for ethical and civic learning - Álvarez Urda, Paula (UNIR, 2026)
Reseña
Ruiz-Corbella, M. y García-Gutiérrez, J. (Eds.) (2023). Aprendizaje-servicio: escenarios de aprendizajes éticos y cívicos
Book review
Keywords: reseña